Does immigration affect the long-term educational outcomes of natives? Quasi-experimental evidence - Eric D. Gould; Victor Lavy; Marco Daniele Paserman (Institute for the Study of Labor (IZA), 2005)
This paper uses the mass migration wave to Israel in the 1990s to examine the impact of immigrant concentration during elementary school on the long-term academic outcomes of native students in high school. To identify the causal effect of immigrant children on their native peers, the empirical strategy must address two sources of bias: the endogenous sorting of immigrants across schools, and the endogenous grade placement of immigrants within schools. We control for the endogeneity of immigrant placement across schools by conditioning on the total number of immigrants in a school and exploit random variation in the number of immigrants across grades within the same school. To address the endogenous grade placement of immigrants within schools, we use the immigrants' dates of birth as an instrument for their actual grade placement. The results suggest that the overall presence of immigrants in a grade had a significant and large adverse effect on two important outcomes for Israeli natives: the dropout rate and the chances of passing the high school matriculation exam which is necessary to attend college.
Keywords: I20; J24; 330; school quality; natural experiment; peer effects; dropout rates; immigrant absorption; Einwanderung; Bildungsverhalten; Allgemeinbildende Schule; Israel